2022
DOI: 10.30794/pausbed.1076301
|View full text |Cite
|
Sign up to set email alerts
|

Specific Factors Affecting Risk-Taking Behaviour: Panel Cointegration and Causality Analysis on Bist Bank Index

Abstract: In the study, it is aimed to investigate the determinants of risk-taking behavior of banks traded in Borsa Istanbul Bank Index in the period of December 2000 - December 2020 by panel cointegration and causality analysis. Risk-taking behavior of banks is measured with Z-Score. Ratios related to financial structure (Equity/Total Asset), asset quality (Net Credit/Total Asset), performance (Net Profit/Total Asset), liquidity (Amihud Ratio) and franchise value ((Market Value + Total Debt) /Total Asset) was included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…The findings show that an increase in the traditional capital ratio increases the ROA in all market conditions. The results obtained in the study are consistent with the findings of Gunes (2014), Lee, Ning and Lee (2015), Okuyan and Karatas (2017), Kocaman et al (2018), Kilic (2019), Coccorese and Girardone (2021), Kaya et al (2022), andBoamah et al(2023); however, it differs from the findings of Nur (2022) and Topak and Talu (2017). They found a negative relationship between the variables.…”
Section: Empirical Results and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings show that an increase in the traditional capital ratio increases the ROA in all market conditions. The results obtained in the study are consistent with the findings of Gunes (2014), Lee, Ning and Lee (2015), Okuyan and Karatas (2017), Kocaman et al (2018), Kilic (2019), Coccorese and Girardone (2021), Kaya et al (2022), andBoamah et al(2023); however, it differs from the findings of Nur (2022) and Topak and Talu (2017). They found a negative relationship between the variables.…”
Section: Empirical Results and Discussionsupporting
confidence: 90%
“…Isik and Belke (2017) studied 13 commercial banks and concluded a negative relationship between traditional capital and risk-taking. In addition, Nur (2022) conducted a study on seven banks traded in Borsa Istanbul and concluded that the relationship between traditional capital and risk-taking is negative.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation